2007
DOI: 10.1371/journal.pone.0001009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Differential N-linked and O-linked Mannosylation on Recognition of Fungal Antigens by Dendritic Cells

Abstract: BackgroundAn experimental approach for improving vaccine efficacy involves targeting antigens to mannose receptors (MRs) on dendritic cells (DCs) and other professional antigen presenting cells. Previously, we demonstrated that mannosylated Pichia pastoris-derived recombinant proteins exhibited increased immunogenicity compared to proteins lacking mannosylation. In order to gain insight into the mechanisms responsible for this observation, the present study examined the cellular uptake of the mannosylated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 32 publications
3
40
0
1
Order By: Relevance
“…Mannosylated fungal antigens (both N-linked and O-linked mannosylated) exhibited increased immunogenicity compared with proteins lacking mannosylation, were taken up by mannose-specific C-type lectin receptors, and colocalized in MHC class II + compartments (57). We found that deglycosylated Pep1p no longer acted as a fungal vaccine capable of activating CD4-dependent memory to the fungus (data not shown), a finding confirming the importance of MR in the rapid internalization and concentration of a variety of glycosylated fungal antigens (57).…”
Section: Discussionmentioning
confidence: 99%
“…Mannosylated fungal antigens (both N-linked and O-linked mannosylated) exhibited increased immunogenicity compared with proteins lacking mannosylation, were taken up by mannose-specific C-type lectin receptors, and colocalized in MHC class II + compartments (57). We found that deglycosylated Pep1p no longer acted as a fungal vaccine capable of activating CD4-dependent memory to the fungus (data not shown), a finding confirming the importance of MR in the rapid internalization and concentration of a variety of glycosylated fungal antigens (57).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that recombinant glycoproteins produced by insect cells, including S2 cells, were glycosylated primarily with simple paucimannosidic N-glycans lacking sialylated antennae that prolong the half-life of glycoproteins in the blood [48][49][50]. Furthermore, it was reported that the macrophage mannose receptor specifically recognizes mannosylated proteins and degrades them through the mannose-specific C-type lectin receptor-dependent process [51]. We concluded that the lack of effectiveness of S2-produced rec-Gth administered in vivo is related to glycantargeted degradation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the MR, murine DCs have other C-type lectin receptors that recognize mannose residues, including DC-specific intercellular adhesion molecule 3 grabbing nonintegrin homologs, langerin and dectin-2 (28). Thus, receptor redundancy and macropinocytosis could explain the lack of difference in MP uptake between the wild-type and MR KO DCs (12,13). After antigen uptake, subsequent processing and presenting of the antigen are necessary for an adaptive immune response.…”
Section: Vol 76 2008 Susceptibility Of Mr Ko Mice To Cryptococcosismentioning
confidence: 99%